Evaluation of Technology Solutions for Municipal Waste Incineration Using LCA Results And Multi-Criteria Analysis - Generowicz, Agnieszka; Henclik, Anna; Kulczycka, Joanna; Kowalski, Zygmunt (Journal of Environmental Accounting and Management, 2026)
Multi-criteria analysis was used to compare technology solutions for 3 chosen municipal waste incineration systems in Warsaw, Tarnobrzeg and Spittelau in Vienna. LCA results were used to calculate the value of the criteria applied in the multi-criteria analysis. The comprehensive comparative assessment of options for incineration of municipal waste took into account, as the partial indicators of impact categories, results obtained from LCA calculation and production cost. The functional unit of the system is 1 tonne of municipal waste treated by incineration. It includes the life cycle from the material and energy used (transport was excluded) based on real data, and from infrastructure based on data from the Ecoinvent database. The system boundaries of the analysis are from ‘cradle’ to ‘gate’. LCA results based on the data obtained were created using the ReCiPe method. As a result of the multi-criteria analysis, a solution was obtained which involved ranking the waste incineration options analysed from the most to least beneficial solution taking into account environmental and economic criteria. For all the options analysed, and using the multi-criteria analysis as well as the LCA method and regardless of the criteria hierarchy adopted, the waste incineration technology in Spittelau is selected as being ultimately more appropriate than the others. Incineration in Spittelau has a higher capacity and lower impact on the environment compared to that in Warsaw and Tarnobrzeg thanks to the highly efficient flue gas treatment systems installed, which are, however, very costly (average installation and running cost).